2008
DOI: 10.1111/j.1365-2869.2008.00662.x
|View full text |Cite
|
Sign up to set email alerts
|

A single night of sleep deprivation increases ghrelin levels and feelings of hunger in normal‐weight healthy men

Abstract: SUMMAR Y Sleep loss is currently proposed to disturb endocrine regulation of energy homeostasis leading to weight gain and obesity. Supporting this view, a reduction of sleep duration to 4 h for two consecutive nights has recently been shown to decrease circulating leptin levels and to increase ghrelin levels, as well as self-reported hunger. We hypothesized that similar endocrine alterations occur even after a single night of sleep restriction. In a balanced order, nine healthy normal-weight men spent three n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
199
7
14

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(236 citation statements)
references
References 16 publications
16
199
7
14
Order By: Relevance
“…We also observed inverse relationships between SWS and feelings of hunger, measured using a visual analog scale, as well as cortisol levels and STAI state scores, used to measure mood, 46,51 while all positive associations with the amount of REM sleep were observed. Regarding SWS, these findings are in concordance to studies using extreme forms of sleep deprivation, which show increased feelings of hunger, 8,16,17 increased ghrelin levels 7,8,15 and increased cortisol levels 21,29 and suggests that subjects were hungrier and more stressed when SWS was relatively short. The positive association between cortisol levels and REM sleep, is complementary to results by van Cauter et al, 35 who observed an inverse relationship between nadir cortisol levels and REM sleep, which suggests a blunted hypothalamic-pituitaryadrenal axis response that has been related to obesity.…”
Section: Discussionsupporting
confidence: 78%
“…We also observed inverse relationships between SWS and feelings of hunger, measured using a visual analog scale, as well as cortisol levels and STAI state scores, used to measure mood, 46,51 while all positive associations with the amount of REM sleep were observed. Regarding SWS, these findings are in concordance to studies using extreme forms of sleep deprivation, which show increased feelings of hunger, 8,16,17 increased ghrelin levels 7,8,15 and increased cortisol levels 21,29 and suggests that subjects were hungrier and more stressed when SWS was relatively short. The positive association between cortisol levels and REM sleep, is complementary to results by van Cauter et al, 35 who observed an inverse relationship between nadir cortisol levels and REM sleep, which suggests a blunted hypothalamic-pituitaryadrenal axis response that has been related to obesity.…”
Section: Discussionsupporting
confidence: 78%
“…Elsewhere, in Kenya and the USA, shorter sleep was associated with obesity in women only [47,48]. Evidence suggests that acute short sleep duration results in an imbalance of hormones controlling hunger and appetite, which in turn, are characterized by decreased leptin (satiety hormone), and increased ghrelin (appetite-stimulating hormone) [49,50]. …”
Section: Discussionmentioning
confidence: 99%
“…Until now the emphasis has been on elucidating biological mechanisms causing short sleep to directly impact obesity (Taheri et al, 2004;Flint et al, 2007;Van Cauter et al, 2007;Schmid et al, 2008;Spruyt, 2011). This exploratory study has highlighted the power of an anthropological perspective to challenge and further our understanding.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that in adults, hormonal mechanisms, appetite regulation and food intake link short sleep with weight gain (Taheri et al, 2004;Van Cauter et al, 2008;Schmid et al, 2008;Knutson 2012). Studies have not been replicated in young childrenalthough short sleep has been linked with child insulin resistance and metabolic marker levels (Flint et al, 2008;Spruyt et al, 2011).…”
Section: Introductionmentioning
confidence: 99%